Detection of Virulence Genes in Enterococci Isolated From the Human Normal Flora by Multiplex-Polymerase Chain Reaction. Issue 4 (July 2016) - Khanmohammadian, Shirin; Enayati, Mohsen; Sadeghi, Javad; Irajian, Gholamreza; Amirmozafari, Nour; Talebi, Malihe
Abstract : Background: Enterococcus species recently evolved from a common avirulent normal flora into a multidrug–resistant, health care–associated pathogen causing difficult-to-treat diseases. The aim of the current study was the detection of aggregation substance ( asa ), hyaluronidase ( hyl ), cytolysin ( cyl ), enterococcal surface protein ( esp ), collagen-binding protein ( acm ), gelatinase ( gelE ), and Enterococcus faecalis endocarditis antigen genes in Enterococcus faecium isolated from healthy volunteers by the Multiplex-polymerase chain reaction (PCR) method. Methods: Stool samples were obtained from 24 healthy volunteers. After biochemical and microbiological tests, all isolates were tested for the presence of the virulence genes by Multiplex-PCR. Results: In total, 91 E. faecium strains were collected from 54 different REP-PCR patterns. The distribution of the virulence genes showed that 33 (36%), 14 (15%), 3 (3%), 1 (1.1%), and 0 isolates were positive for acm, asa, esp, cylA, hyl, and gelE genes, respectively. Conclusions: Despite the fact that E. faecium isolated from normal human intestines usually shows low incidence of virulence genes, they may act as harbors of virulence factors, allowing the distribution of these genes to the human normal flora through the food chain.